ASPEK PSIKOLOGI DAN KESEHATAN MENTAL DALAM PENDIDIKAN AQIDAH DAN IBADAH PESERTA DIDIK - Ahmad Syarifin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
The issue of aqeedah and psychological aspects, as well as mental health in it are human needs. On the other hand, the highest needs of human beings are religion, religion is identical with belief, this belief is understood as a faith which in Islam manifests in the six pillars  of faith. Psychologically humans need religion and  one of the characteristics that  humans are healthy is by the existence of religion. One of the mental health can be achieved through the Islamic method, through the correct implementation of the pillars of faith in daily life, so that the faith is not only imprinted in the heart, but is spoken with verbally  and  concretely in its behavior. The psychological aspects of worship can be seen from  the  nature of worship education itself. The essence is like the  birth in man (psychologically) of the  intensity of consciousness in thinking, then a Muslim wherever he is will feel bound to such  ties of consciousness, therefore hu- mans will act systematically based on honesty and  self-confidence. In addition, Muslims who feel bound by Allah will feel the delicacy and attitude of prioritizing God as a source, with worship like this that humans will have identity (self- development), because unity has strengthened itself